Avaliação do efeito do etanol e do ácido acético na corrosão do aço carbono por CO2 em condições de não-formação de filmes protetores - Guisso, Ricardo Marcondes (2013)
The natural gas produced in offshore platforms is sent to shore through pipelines made of carbon steel. This gas with water and corrosive agents such as dioxide gas and acetic acid are corrosive to carbon steel. Ethanol is usually injected continuously to prevent "hydrate" formation in the pipelines. This paper aims to analyze the effect of acetic acid in different concentrations and shear stresses on the corrosion of carbon steel, as well as the inhibitor effect of ethanol on corrosion in conditions of non-formation of protective films. It was found that the presence of acetic acid inhibits the anodic reaction and increases the limiting current cathodic in the corrosion process of carbon steel. These effects compete among themselves and affect the corrosion rate. It has been proved that the inhibitor action of ethanol in the corrosion process, is attributed to the increase in solution resistivity and a decrease in the acid strength of the protons. Despite the addition of ethanol had decreased of the rates of uniform corrosion in carbon steel, it was observed localized corrosion in the specimens. The conclusion is that the acetic acid plays a fundamental role in the corrosion process of carbon steel and that ethanol inhibits the uniform corrosion, but further tests are required to investigate the process of localized corrosion in these conditions